KEJADIAN HIPERBILIRUBINEMIA PADA NEONATUS DI RSUD PROF. DR. MARGONO SOEKARDJO PURWOKERTO TAHUN 2012 - Tin Utami (Universitas Harapan Bangsa Purwokerto, 2013)
his study aimed to determine the incidence of hyperbilirubinemia in neonates inhospitals Prof. Dr. Margono Soekardjo Purwokerto in 2012Methods This research is descriptive Retrospective Study. Samples of thisresearch is data rekamedis neonates in hospitals Prof. Dr. Margono SoekarjoPurwokerto with 100 respondents drawn using quota sampling technique.The results of this study are medical records obtained neonates in hospitals Prof.Dr. Margono Soekarjo Purwokerto in 2012 from 100 the data contained 48neonates who had hyperbilirubinemia (48%).The conclusion in this study that only 48% of neonates in hospitals Prof. dr.Margono Soekarjo Purwokerto experience of 100 neonatal hyperbilirubinemia. Keywords: Genesis hyperbilirubinemia, neonatal.